2013
DOI: 10.1161/circheartfailure.112.000112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Features Associated With Improvement in Mitral Regurgitation After Cardiac Resynchronization Therapy and Their Relation to Long-Term Patient Outcome

Abstract: Background-Mechanisms of mitral regurgitation (MR) reduction with cardiac resynchronization therapy (CRT) are complex, and their association with long-term outcome is unclear. We sought to elucidate mechanistic features of reduction in MR with CRT, which impact long-term patient survival. Methods and Results-A prospective longitudinal study of 277 patients with heart failure with QRS width ≥120 ms and ejection fraction ≤35% for CRT was performed. Quantitative echocardiography, including dyssynchrony analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 45 publications
8
47
0
1
Order By: Relevance
“…Others have similarly identified immediate reductions in MR post CRT 5 and identified baseline mechanical dyssynchrony as a significant predictor of MR reduction. 3 In contrast, Madaric et al 24 identified 3-month LVRR as a more important predictor of MR reduction (rest and exercise) when compared with immediate reduction in mechanical dyssynchrony after CRT. To date, analyses of CRT and MR have been limited by the retrospective, post hoc evaluation of MR at varying time points after implant, 4,5 the absence of serial echocardiography at intermediate time points (eg, 3 months post implant), 3 or significant limitation in sample size (<100 patients).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Others have similarly identified immediate reductions in MR post CRT 5 and identified baseline mechanical dyssynchrony as a significant predictor of MR reduction. 3 In contrast, Madaric et al 24 identified 3-month LVRR as a more important predictor of MR reduction (rest and exercise) when compared with immediate reduction in mechanical dyssynchrony after CRT. To date, analyses of CRT and MR have been limited by the retrospective, post hoc evaluation of MR at varying time points after implant, 4,5 the absence of serial echocardiography at intermediate time points (eg, 3 months post implant), 3 or significant limitation in sample size (<100 patients).…”
Section: Discussionmentioning
confidence: 93%
“…3 In contrast, Madaric et al 24 identified 3-month LVRR as a more important predictor of MR reduction (rest and exercise) when compared with immediate reduction in mechanical dyssynchrony after CRT. To date, analyses of CRT and MR have been limited by the retrospective, post hoc evaluation of MR at varying time points after implant, 4,5 the absence of serial echocardiography at intermediate time points (eg, 3 months post implant), 3 or significant limitation in sample size (<100 patients). 3,24 Strengths of this study include its size and related power to detect significant mechanistic associations, the prospective availability of serial echocardiography with dyssynchrony assessment nested within a randomized controlled trial, and complementary multimodal analysis of MR reduction (linear and logistic models) accounting for regression to the mean with adjustment for baseline MR. We also uniquely assessed the impact of a clinically relevant intervention (ie, QLV-based pacing strategy) associated with both proposed mediators of MR reduction (ie, LVRR and mechanical resynchronization).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations